Ultrasonography I: Development of Ovarian Follicles in Boer Goats Superovulated With pFSH Containing 40 % pLH - Suyadi Suyadi (Media Veteriner, 1998)
Response of oestrus in Boer goats and development of ovarian follicle to superovulatory treatment were studied. All goats (n= 17) received subcutaneous progesterone ear implant for 11 days to synchronize oestrus cycle. Forty eight hours before implant removal and the following 3 days. 16 AU pFSH containing 40 % pLH was injected 6 times (4, 4; 2, 2; 2, 2) in 12 h intervals. Goats received PGF2a twice synchronized with FSH treatments to induce luteolysis (5 mg PGF2a of each) 24 h after implant removal. Animals were checked for oestrus with an aproned buck 3 times a day. During standing oestrus animals were naturally mated 2 or 3 times. Follicular development and ovulation were monitored 2 times a day using transrectal ultrasonography equipped with a 7.5 MHz linear-array transducer. This evaluation began from the time of implant removal until 48 h after the end of oestrus. Eighty eight per cent of animal showed oestrus with mean of the onset of oestrus 33 h after implant removal and oestrus duration of 30 h. Eighty two percent of does had corpora lutea with number of 11,0 and persistent follicles of 2.1 at laparoscopic examination on day 6 after the end of oestrus. The maximum number of follicles with diameter ≥ 2 mm recorded at the observation of 36 and 48 h after implant removal, whereas those with ≥ 6 mm in diameter were 48 - 60 h. The number of follicles with diameter 2 - 3 mm and 4 - 5 mm during observation period were constant. The ovulation of follicles did not occur spontaneously but they ovulated in several periods. The pFSH+ 40 % pLH preparation yielded a sufficient result for superovulation means in Boer goats. For monitoring the response of ovaries to the superovulatory treatment, ultrasonography was a simple and effective method.